1996
DOI: 10.1111/j.1600-065x.1996.tb00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Thymus‐Dependent Form of Tolerance that is Not Based on Elimination or Anergy of Reactive T cells

Abstract: The avian embryo has provided an appropriate model to study the ontogeny of the primary lymphoid organs, thymus and bursa of Fabricius. By using the quail-chick marker system the embryonic origin of the highly intricate cell components which form these organs could be traced back to the initial endodermal, mesodermal and ectodermal germ layers. The timing and dynamics of the incoming and outcoming flows of hemopoietic cells which characterize their lymphopoietic activity could be revealed in both quail and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 58 publications
4
69
0
2
Order By: Relevance
“…Yet there are other important studies that have contributed to our current conceptualization of T R cells. For example, dominant transplantation tolerance can be established by administration of anti-CD4 or other mAb, the immunosuppressant cyclosporine A, or transplanting allogeneic or xenogeneic thymic epithelial cells into embryos [72][73][74]. There is recent evidence that these types of graft tolerance are maintained by suppressive CD4 + T cells, which are functionally and phenotypically similar to Foxp3 + natural T R cells [75].…”
Section: Discussionmentioning
confidence: 99%
“…Yet there are other important studies that have contributed to our current conceptualization of T R cells. For example, dominant transplantation tolerance can be established by administration of anti-CD4 or other mAb, the immunosuppressant cyclosporine A, or transplanting allogeneic or xenogeneic thymic epithelial cells into embryos [72][73][74]. There is recent evidence that these types of graft tolerance are maintained by suppressive CD4 + T cells, which are functionally and phenotypically similar to Foxp3 + natural T R cells [75].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of autoimmunity provoked by neonatal thymectomy in mice (1), and of transplantation tolerance to tissue grafts induced by previous transplantation of pure thymic epithelium in birds and in mice (9), indicated that natural T reg represent a distinct thymus-committed lineage. Although it has also become evident that further Foxp3 ϩ T reg can be generated from peripheral naïve CD4 ϩ T cells upon ''tolerogenic'' antigen presentation in vivo or activation in the presence of transforming growth factor (TGF)-␤ in vitro (10,11), this notion of a stable lineage has been strengthened by data showing that the phenotypic and functional features of CD4 ϩ CD25 ϩ T reg are stably maintained after many rounds of cell division in vitro and in vivo (1).…”
mentioning
confidence: 99%
“…This is wrong on two accounts. First, other tissue grafts, such as skin, at birth or even in utero [11] fail to induce tolerance to themselves, as first pointed out by Billingham & Silvers [19] but previously reported by Medawar & Woodruff [20], and then extensively confirmed in birds [14]. Second, as later confirmed by other investigators [21], TE does induce tolerance to other tissues, if transplanted into allogeneic, athymic mice.…”
mentioning
confidence: 75%
“…The original work of Le Douarin and colleagues in birds, as well as its developments in the mouse, have established that TE establishes tolerance towards a variety of peripheral tissues (all ? ), except haemopoietic cells [11,12] †. This tolerance is robust, and cannot be abrogated by repeated priming with 'professional' antigen-presenting cells, before or after tissue grafts [12].…”
mentioning
confidence: 99%